The Impact of Low-Temperature Inactivation of Protease AprX from Pseudomonas on Its Proteolytic Capacity and Specificity: A Peptidomic Study - Chunyue Zhang; Sjef Boeren; Liming Zhao; Etske Bijl; Kasper Hettinga (Dairy, 2023)
The destabilization of UHT milk during its shelf life can be promoted by the residual proteolytic activity attributed to the protease AprX from Pseudomonas. To better understand the hydrolysis patterns of AprX, and to evaluate the feasibility of using low-temperature inactivation (LTI) for AprX, the release of peptides through AprX activity on milk proteins was examined using an LC-MS/MS-based peptidomic analysis. Milk samples were either directly incubated to be hydrolyzed by AprX, or preheated under LTI conditions (60 °C for 15 min) and then incubated. Peptides and parent proteins (the proteins from which the peptides originated) were identified and quantified. The peptides were mapped and the cleavage frequency of amino acids in the P1/P1′ positions was analyzed, after which the influence of LTI and the potential bitterness of the formed peptides were determined. Our results showed that a total of 2488 peptides were identified from 48 parent proteins, with the most abundant peptides originating from κ-casein and β-casein. AprX may also non-specifically hydrolyze other proteins in milk. Except for decreasing the bitterness potential in skim UHT milk, LTI did not significantly reduce the AprX-induced hydrolysis of milk proteins. Therefore, the inactivation of AprX by LTI may not be feasible in UHT milk production.